A comparison of plasma glucose and oxidative status in lactating dairy cows in summer and autumn. (21st January 2016) - Kurokawa, Yuzo; Yamashita, Rina; Okita, Miki; Yoshitoshi, Rena; Sugino, Toshihisa; Obitsu, Taketo; Kawamura, Kensuke
Abstract: The objective of this study was to investigate the effects of the hot summer season on plasma glucose and oxidative stress markers. For two 14‐day experimental periods, namely periods 1 (July‐August) and 2 (October‐November), 12 and 14 lactating dairy cows, respectively, that were milked using an automatic milking system, were fed diets containing similar ingredients, and their milk production, plasma metabolites and oxidative status markers were investigated. Dry matter intake and milk yield were not affected by the experimental period. Rectal temperature at 18.00 hours and milk protein concentration in period 1 were higher and lower, respectively, than in period 2 ( P < 0.05), suggesting that the hot summer season had an effect on the experimental dairy cows. Plasma glucose and the ascorbic acid + dehydroascorbic acid (AA) concentrations in period 1 were lower than in period 2 ( P < 0.01). The plasma malondialdehyde (MDA) concentration did not differ between the experimental periods. The increase in the cellular AA uptake in peripheral tissues in period 1 might be a possible compensatory mechanism to balance the occurrence of reactive oxygen species and the antioxidant capacity in the cells, resulting in the absence of an effect of the hot summer season on plasma MDA concentration. © 2016 Japanese Society of Animal Science